2015
DOI: 10.4314/tjpr.v14i10.20
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Volatile Compounds of <i>Illicium verum </i>Hook. f. Using Simultaneous Distillation-Extraction and Solid Phase Microextraction Coupled with Gas Chromatography-Mass Spectrometry

Abstract: Purpose: To determine the characteristic aromatic constituents of star anise (Illicium verum Hook. f.) and identify its main aroma compounds for sensory evaluation. Methods: The volatile compounds of star anise were prepared by simultaneous distillation-extraction (SDE) and the compounds were identified by gas chromatography-mass spectroscopy (GC-MS). The flavor compounds were confirmed by gas chromatography-olfactometry (GC-O). Their flavor dilution factor (FD) values were determined using aroma extract di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…Fagundes et al (2014) concluded that anethole in the essential oil of Illium verum Hook can be identified and determined by GC-MS, NMR and UV-VIS, and a superior HPLC method has been developed for the determination of the compound in rat plasma. Zhang et al (2015) have examined the characteristics aromatic constituents of star anise, and they have confirmed forty seven compounds, with trans-anethole, estragole, and anisaldehyde the main aroma components. The content of trans-anethole was the highest (75.76%), followed by linalool (1.44%), Limonen (1.01%), and 4 , -methoxypropiophenone (0.72%) were the lowest.…”
Section: Modern Medicinal Usage Of Star Anisementioning
confidence: 98%
“…Fagundes et al (2014) concluded that anethole in the essential oil of Illium verum Hook can be identified and determined by GC-MS, NMR and UV-VIS, and a superior HPLC method has been developed for the determination of the compound in rat plasma. Zhang et al (2015) have examined the characteristics aromatic constituents of star anise, and they have confirmed forty seven compounds, with trans-anethole, estragole, and anisaldehyde the main aroma components. The content of trans-anethole was the highest (75.76%), followed by linalool (1.44%), Limonen (1.01%), and 4 , -methoxypropiophenone (0.72%) were the lowest.…”
Section: Modern Medicinal Usage Of Star Anisementioning
confidence: 98%
“…The mass spectrometer was operated in the electron impact ionization mode. The chromatographic spectrum was analysed based on NIST08.L database of the MSDChem workstation ( Zhang et al . 2015 ).…”
Section: Methodsmentioning
confidence: 99%
“…compounds including p-anisaldehyde (33,FD 262,144). This compound, as well as (E)methyl cinnamate (34, FD 1024) and methyl p-anisate (35,FD 4096), is well known for cultures of PSA [4,12,15]. In the culture extract of CSSM PSA Mk 37, additional aromatic compounds, including anisole (11, FD 1024), benzaldehyde (18, FD 1024), p-methylacetophenone (27, FD 2048), methyl p-anisate (35,FD 4096), p-methoxyphenylacetone (37, FD 512), p-methoxypropiophenone (38, FD 1024), p-methoxybenzyl alcohol (40, FD 512), 3,4dimethoxybenzaldehyde (43, FD 8192), and 2-hydroxy-1-(4-methoxyphenyl)-1-propanone (48, FD 512), were detected (Figure 3).…”
Section: Aroma Extract Dilution Analysis and Compound Identificationmentioning
confidence: 99%
“…AEDA indicated that p-anisaldehyde (33, FD 262,144) was a key aroma compound, contributing to the distinct sweetish, anisic, and herbaceous notes of the overall aroma. In plants, p-anisaldehyde is found in fennel, aniseed, and also in vanilla [32][33][34][35][36][37][38][39]. Depending on the study, 0.3 mg kg −1 to 132 mg kg −1 of p-anisaldehyde have been quantified in vanilla beans [37][38][39].…”
Section: Aroma Extract Dilution Analysis and Compound Identificationmentioning
confidence: 99%